Kodifikasi al-Qur’an: Studi atas Pemikiran John Burton - Miftahul Janah (At-Ta'wil: Jurnal Pengkajian al-Qur'an dan at-Turats, 2019)
As the object of study, the Qur'an is not something exclusive to Muslims. Many orientalists study the Qur'an, one of them is John Burton. in his study, he argues that the traditions related to the codification of the Qur'an are incorrect. With the result that the codification of the Qur'an does not refer to the caliphs, but is done by the Prophet himself. The argument is built on two nasikh-mansukh concepts used by Usul Fiqh scholars in exploring Islamic law. Depart from that, this paper will discuss; first, the basic assumption of John Burton, second, John Burton's thought of the codification of the Qur'an, the third, the frailty of John Burton's thought about the study of the Qur'an, especially the codification of the Qur'an.